Genetic variability studies in sesame (Sesamum indicum L.): Genetic variability studies in sesame (Sesamum indicum L.) - D PADMAJA; M RAJENDRAPRASAD; R UMA REDDY (Journal of Oilseeds Research, 2023)
The field experiment was conducted during summer, 2019-20 at Regional Agricultural Research Station, Polasa, Jagtial India. To access genetic variability, heritability and genetic advance for seed yield and its attributing traits in 18 genotypes of sesame. The present investigation was carried out to evaluate the sesame genotypes for variability on yield with yield attributing traits. Seed yield exhibited low heritability, coupled with low genetic advance as per cent of mean, GCV values representing the availability of less variability for this trait. 1000 seed weight and days to 50% flowering recorded high heritability coupled with moderate genetic advance as per cent mean. Results reveal that, these characters were under the governance of additive gene action and can be further improved through selection procedure.